The Association of the Quality of Work Life and General Health of the Nurses in Psychiatric Wards - L Esmaeilpour; E Jafarjalal (Iran University of Medical Sciences, 2019)
Background & Aims: The level of tension and stress is comparatively higher in psychiatric units due to the nature of the disorders and conditions of the patients under treatment, which could threaten various aspects of the general health of psychiatric nurses. Furthermore, this issue could adversely affect the quality of work life in nurses. The present study aimed to investigate the association between the quality of work life and general health of the nurses in the psychiatric wards of the teaching hospitals affiliated to the medical universities in Tehran, Iran. Materials & Methods: This descriptive-correlational study was conducted on 200 nurses engaged in the psychiatric wards of the teaching hospitals affiliated to the medical universities in Tehran. The participants were selected via stratified random sampling. Data were collected using the quality of work life questionnaire and general health questionnaire. Data analysis was performed in SPSS version 20 using descriptive and inferential statistics, including Pearson's correlation-coefficient, independent t-test, and the analysis of variance (ANOVA). Results: The mean scores of the quality of work life and general health of the nurses were moderate and favorable, respectively. Significant inverse correlations were observed between the quality of work life and general health in the dimensions of anxiety and sleep disorders (P=0.026) and depressive symptoms (P=0.041), so that the increased quality of work life could reduce the scores of these dimensions of general health. Conclusion: According to the results, the quality of work life could affect the general health of psychiatric nurses in terms of anxiety, depressive symptoms, and sleep disorders. Therefore, the adoption of effective policies to improve the quality of work life could positively influence the general health of the nurses employed in psychiatric wards.